Invasive lobular carcinoma of the breast presenting as retroperitoneal fibrosis: a case report - Al-Haddad Sahar; Gabril Manal Y; Yousef George M; Mulligan Anna; Honey R John (Journal of Medical Case Reports, 2010)
Abstract Introduction Invasive lobular carcinoma of the breast represents approximately 6.3% of mammary malignancies. Distant metastasis of invasive lobular carcinoma to the peritoneum or retroperitoneum has been reported fairly frequently. Case presentation We report the case of a 59-year-old Caucasian-Canadian woman with invasive lobular carcinoma of the breast presenting with retroperitoneal fibrosis and bilateral ureteral obstruction. Intra-operative pathology consultation did not reveal malignancy. The diagnosis, however, was confirmed on permanent sections by histological appearance in addition to immunohistochemistry. To the best of our knowledge, this is the first reported case of invasive lobular carcinoma of the breast presenting with retroperitoneal fibrosis. Conclusion In a case of unexplained ureteric obstruction and retroperitoneal fibrosis, more comprehensive physical examination and additional ancillary studies may be warranted to rule out malignancy as an underlying etiology. This case also emphasizes that intra-operative frozen section consultation cannot always be fully relied upon to exclude a malignancy as the etiology of retroperitoneal fibrosis. Moreover, in permanent histopathology sections, immunohistochemistry testing can be of value to rule out metastatic disease where the morphology is not salient. There is a need for a thorough physical examination of patients with retroperitoneal fibrosis, including the breast and gynecological organs.